AZ32 Reverses ABCG2-Mediated Multidrug Resistance in Colorectal Cancer - Liu, Kun; Li, Yan-Chi; Chen, Yu; Shi, Xiao-Bao; Xing, Zi-Hao; He, Zheng-Jie; Wang, Sheng-Te; Liu, Wei-Jing; Zhang, Peng-Wei; Yu, Ze-Zhong; Mo, Xue-Mei; Chen, Mei-Wan; et al. (Frontiers in Oncology, 2021)
Colorectal cancer is a common malignancy with the third highest incidence and second highest mortality rate among all cancers in the world. Chemotherapy resistance in colorectal cancer is an essential factor leading to the high mortality rate. The ATP-binding cassette (ABC) superfamily G member 2 (ABCG2) confers multidrug resistance (MDR) to a range of chemotherapeutic agents by decreasing their intracellular content. The development of novel ABCG2 inhibitors has emerged as a tractable strategy to circumvent drug resistance. In this study, an ABCG2-knockout colorectal cancer cell line was established to assist inhibitor screening. Additionally, we found that ataxia-telangiectasia mutated (ATM) kinase inhibitor AZ32 could sensitize ABCG2-overexpressing colorectal cancer cells to ABCG2 substrate chemotherapeutic drugs mitoxantrone and doxorubicin by retaining them inside cells. Western blot assay showed that AZ32 did not alter the expression of ABCG2. Moreover, molecule docking analysis predicted that AZ32 stably located in the transmembrane domain of ABCG2. In conclusion, our result demonstrated that AZ32 could potently reverse ABCG2-mediated MDR in colorectal cancer.